Lower Termite Associations with Microbes: Synergy, Protection, and Interplay - Peterson, Brittany F.; Scharf, Michael E. (Frontiers in Microbiology, 2016)
Lower-termites are one of the best studied symbiotic systems in insects. Their ability to feed on a nitrogen-poor, wood-based diet with help from symbiotic microbes has been under investigation for almost a century. A unique microbial consortium living in the guts of lower termites is essential for wood-feeding, host and symbiont cellulolytic enzymes synergize each other in the termite gut to increase digestive efficiency. Because of their critical role in digestion, gut microbiota are driving forces in all aspects termite biology. Social living also comes with risks for termites. The combination of group living and a microbe-rich habitat makes termites potentially vulnerable to pathogenic infections; however, the use of entomopathogens for termite control has been largely unsuccessful. One mechanism for this failure may be symbiotic collaboration; i.e., one of the very reasons termites have thrived in the first place. Symbiont contributions are thought to neutralize fungal spores as they pass through the termite gut. Also, when the symbiont community is disrupted pathogen susceptibility increases. These recent discoveries have shed light on novel interactions for symbiotic microbes both within the termite host and with pathogenic invaders. Lower-termite biology is therefore tightly linked to symbiotic associations and their resulting physiological collaborations.